What if the Problem Is that There Is too much Critique? - Jonjo Brady (Media Theory)
How to tell “good” critique from “bad” critique, meaningful encounter from opinionated tokenism, or a genuine investment in political emancipation from the cartoonish contrivances of a recuperated emancipatory gesture refolded as empty pastiche? This paper begins with the assumption that we can no longer make any such distinctions. What if all critique nowadays is a spectacle, or perhaps better described, not as critique at all, but merely the proliferation of opinion and criticism? Merely the “unreflective to-and-fro of claim and counter-claim” (MacKenzie, 2004: 6), the “anarchic debris of [already] circulated knowledge” (Badiou, 2001: 50), mere “propositions ... defined by their reference” (Deleuze and Guattari, 1994: 22), by the relationships with what has been said before and what will be inevitably said after. What if the pertinent question is not whether we can tell “good” critique from “bad” critique, but in the wake of all contemporary communication becoming repetitive and impotent, why do we insist on talking at all? And what if, in light of all this, the only potentially radical response is to remain silent? To find “little gaps of solitude and silence in which they might eventually find something to say” (Deleuze, 1997: 129). A conjuring of the gentleness, the quiet solemnity and the right to have nothing to say is perhaps the condition that has a “chance of framing the rare, or even rarer, thing that might be worth saying” (Deleuze, 1997: 129).